The microbiome in preterm birth. (October 2018) - Chu, Derrick M.; Seferovic, Maxim; Pace, Ryan M.; Aagaard, Kjersti M.
Abstract: The microbiome is thought to play a role in the maintenance of a healthy pregnancy and thus may either contribute to or protect from preterm birth. Study of the human microbiome has been aided by metagenomic sequencing approaches, providing greater insight into the commensal bacteria that coexist in and on our bodies. The vaginal microbiome has been the most widely studied, though there have been recent efforts to explore the gut, cervical-vaginal, placental and oral microbiomes in the further search of etiologies of preterm birth. To date, a specific microbiome community or microorganism has yet to be reliably associated with preterm birth. This is partly due to the fact that the 'normal' constituents' microbiome can vary widely between healthy individuals. Before our knowledge of the microbiome can be utilized and applied in clinical practice, a greater understanding of the 'healthy' microbiome must be achieved. In particular, we must first appreciate how our microbes influence our biology to promote a healthy pregnancy or alternately render preterm birth.